Cardiovascular Cast Model Fabrication and Casting Effectiveness Evaluation in Fetus with Severe Congenital Heart Disease or Normal Heart - 王瑜 曹海燕 谢明星 贺林 韩伟 洪柳 彭源 胡云飞 宋本才 王静 王斌 邓诚 (Journal of Huazhong University of Science and Technology. Medical sciences, 2016)
To investigate the application and effectiveness of vascular corrosion technique in preparing fetal cardiovascular cast models, 10 normal fetal heart specimens with other congenital disease（control group） and 18 specimens with severe congenital heart disease（case group） from induced abortions were enrolled in this study from March 2013 to June 2015 in our hospital. Cast models were prepared by injecting casting material into vascular lumen to demonstrate real geometries of fetal cardiovascular system. Casting effectiveness was analyzed in terms of local anatomic structures and different anatomical levels（including overall level, atrioventricular and great vascular system, left-sided and right-sided heart）, as well as different trimesters of pregnancy. In our study, all specimens were successfully casted. Casting effectiveness analysis of local anatomic structures showed a mean score from 1.90±1.45 to 3.60±0.52, without significant differences between case and control groups in most local anatomic structures except left ventricle, which had a higher score in control group（P=0.027）. Inter-group comparison of casting effectiveness in different anatomical levels showed no significant differences between the two groups. Intra-group comparison also revealed undifferentiated casting effectiveness between atrioventricular and great vascular system, or left-sided and right-sided heart in corresponding group. Third-trimester group had a significantly higher perfusion score in great vascular system than second-trimester group（P=0.046）, while the other anatomical levels displayed no such difference. Vascular corrosion technique can be successfully used in fabrication of fetal cardiovascular cast model. It is also a reliable method to demonstrate three-dimensional anatomy of severe congenital heart disease and normal heart in fetus.